New Methods of Teaching at Russian Universities in the Context of Society Digitalization - Reshetnikova, O.E. (KnE Social Sciences, 2021)
The article provides a classification of new teaching methods used by university teachers in order to adapt students to learn new material in the context of their cognitive activities. In modern conditions of the rapid development of digital technologies, it is becoming increasingly difficult to navigate the growing flow of information, so teachers are faced with the problem of helping students learn more effectively, especially if students lack knowledge of new digital technologies. Therefore, the function of the teacher is changing significantly, and there is a need to use such teaching methods that help students more easily and quickly recognize reliable sources, at the same time acquiring the ability to set the necessary search queries and navigate through digital space. New learning technologies, such as gamification, blended learning, mobile learning, micro-learning, project-based learning and facilitation sessions, contribute to the active teacher-student interaction and the formation of new knowledge and competencies. At the same time, the process of acquiring knowledge becomes secondary, and the acquisition of new competencies that will be necessary in future professional life comes to the fore. The digital educational landscape offers students a greater choice, which actualizes the promotion of new educational technologies in the modern university space. Keywords: new teaching methods, digitalization, Russian universities, blended learning, gamification